Ultrasound Triggered Co‐Delivery of Therapeutic MicroRNAs and a Triple Suicide Gene Therapy Vector by Using Biocompatible Polymer Nanoparticles for Improved Cancer Therapy in Mouse Models (Adv. Therap. 5/2021). Issue 5 (10th May 2021) - Kumar, Sukumar Uday; Wang, Huaijun; Telichko, Arsenii V.; Natarajan, Arutselvan; Bettinger, Thierry; Cherkaoui, Samir; Massoud, Tarik F.; Dahl, Jeremy J.; Paulmurugan, Ramasamy
Abstract : A simple and noninvasive targeted delivery of nanomaterials can drive new advancements in cancer nanomedicine. In article number 2000197, Ramasamy Paulmurugan and co‐workers in collaboration with Bracco Suisse SA have demonstrated ultrasound assisted targeted delivery of therapeutic microRNAs and triple therapeutic genes loaded PLGA‐PEG‐PEI nanoparticles to HCC and TNBC tumors in immunocompetent syngeneic mouse models for effective cancer gene therapy.